2022
DOI: 10.26866/jees.2022.4.r.107
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized Implantable Antenna for Wireless Power Transfer and Communication in Biomedical Applications

Abstract: A miniaturized, triple-band, implantable antenna for biomedical applications is presented in this paper. The proposed antenna with dimensions of 8.1 mm × 8.1 mm × 0.64 mm, combined with a shorting pin and a ground slot, operates at bands between 401–406 MHz for the medical implant communications service (MICS); 1,395–1,400 MHz and 1,427–1,432 MHz for the wireless medical telemetry service (WMTS); and 2,400–2,500 MHz for industrial, scientific, and medical (ISM) applications. The antenna is deployed simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Smaller devices are less likely to cause irritation or discomfort to the patient and can be implanted in less invasive ways, via a small incision or injection . This can increase patient acceptance and reduce the risk of complications, ultimately enabling widespread use to capture holistic insight in patient health, and because of continuous power influx, enable computation and communication well beyond contemporary implants. Challenges for miniaturization are mainly in power supply strategies (discussed in Sections “Power Casting Techniques” and “Power Harvesting Techniques”), integration density governed by fabrication challenges (discussed in Section “Fabrication Techniques for Implantable Devices”), and communication and computation (discussed in Sections “Wireless Communication” and “Infrastructure Integration”).…”
Section: Introductionmentioning
confidence: 99%
“…Smaller devices are less likely to cause irritation or discomfort to the patient and can be implanted in less invasive ways, via a small incision or injection . This can increase patient acceptance and reduce the risk of complications, ultimately enabling widespread use to capture holistic insight in patient health, and because of continuous power influx, enable computation and communication well beyond contemporary implants. Challenges for miniaturization are mainly in power supply strategies (discussed in Sections “Power Casting Techniques” and “Power Harvesting Techniques”), integration density governed by fabrication challenges (discussed in Section “Fabrication Techniques for Implantable Devices”), and communication and computation (discussed in Sections “Wireless Communication” and “Infrastructure Integration”).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is known that an antenna with compact size is always popular since it can save space for other components in an equipment. After literature review, it is found that typical approaches to miniaturize antenna size include adopting shorting pins [17][18][19][20], bending technique [21][22][23], loading metasurface structures [24][25][26], accepting fractal structures [27][28][29], etc. In particular, a U-slot patch antenna is halved by loading shorting pins in its center [17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a U-slot patch antenna is halved by loading shorting pins in its center [17]. Combining with a shorting pin and a ground slot, a miniaturized triple-band implantable antenna for biomedical applications is presented in [18]. In [21], size reduction is achieved by employing a modified meandered slot.…”
Section: Introductionmentioning
confidence: 99%
“…The design of implantable antennas is challenging owing to size constraints, the complex, and lossy nature of the human body, resulting in antenna properties that differ from those in free space [10]. Various types of implantable antennas, such as quad-band [11], [12], tripleband [10], [13], dual-band [4], [14], single-band [15], [16], and wide-band [17], [18] antennas, were recently suggested to satisfy the requirements of compactness, acceptable radiation, safety, and reliable link performance. However, these designs feature a single-input singleoutput (SISO) arrangement.…”
Section: Introductionmentioning
confidence: 99%